2021
DOI: 10.52279/jlss.03.02.8792
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualization of the Penology System under Islamic Criminal Law

Abstract: Islam propounds a culture where everybody follows the rules. Islam aims to preserve peace and tranquillity within the society and thus takes all required legal action to ensure the community against disruptive elements. The notion of retribution in Islam is not the primary law of Islam. They are only imposed as a requirement or series and a vindication of the primary structure of Islamic society. Criminal activity within the revered Islamic order of society is not condoned. Islam aims to change the world by ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…All the twenty-five (25) retained items were further pilot tested on three hundred ten (310) public secondary school teachers working in the school education department since Ramzan and Khurram (2023) reported that ten to fifteen respondents are mandatory on each item of the instrument being pilot tested. Sattar, Khurram, and Asif (2023) reported that PLS Smart version 4 is a reliable tool. Therefore, the data analysis of the items of the tool gained by pilot testing was completed using PLS Smart version 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the twenty-five (25) retained items were further pilot tested on three hundred ten (310) public secondary school teachers working in the school education department since Ramzan and Khurram (2023) reported that ten to fifteen respondents are mandatory on each item of the instrument being pilot tested. Sattar, Khurram, and Asif (2023) reported that PLS Smart version 4 is a reliable tool. Therefore, the data analysis of the items of the tool gained by pilot testing was completed using PLS Smart version 4.…”
Section: Resultsmentioning
confidence: 99%
“…Questionnaire TCMQSattar et al (2023) reported two critical tests to ensure the validity of a construct: Convergent Validity and Discriminant Validity. They emphasize that testing is the route to establishing Construct Validity.…”
mentioning
confidence: 99%
“…Second, the imposition of punishment can eliminate the natural rights of each individual. Natural rights are the most basic (fundamental) rights that exist and are inherent in every individual in line with human nature (Safdar et al, 2021); (Lopa, 1996: 2). This right shall be protected and not be violated by anyone.…”
Section: Sanctions For Apostasy and Implications In Human Rights Normsmentioning
confidence: 99%